A single-cell transcriptomic atlas of primate pancreatic islet aging. Issue 2 (10th June 2020) - Li, Jingyi; Zheng, Yuxuan; Yan, Pengze; Song, Moshi; Wang, Si; Sun, Liang; Liu, Zunpeng; Ma, Shuai; Izpisua Belmonte, Juan Carlos; Chan, Piu; Zhou, Qi; Zhang, Weiqi; et al.
Abstract: Aging-related degeneration of pancreatic islet cells contributes to impaired glucose tolerance and diabetes. Endocrine cells age heterogeneously, complicating the efforts to unravel the molecular drivers underlying endocrine aging. To overcome these obstacles, we undertook single-cell RNA sequencing of pancreatic islet cells obtained from young and aged non-diabetic cynomolgus monkeys. Despite sex differences and increased transcriptional variations, aged β-cells showed increased unfolded protein response (UPR) along with the accumulation of protein aggregates. We observed transcriptomic dysregulation of UPR components linked to canonical ATF6 and IRE1 signaling pathways, comprising adaptive UPR during pancreatic aging. Notably, we found aging-related β-cell-specific upregulation of HSP90B1, an endoplasmic reticulum-located chaperone, impeded high glucose-induced insulin secretion. Our work decodes aging-associated transcriptomic changes that underlie pancreatic islet functional decay at single-cell resolution and indicates that targeting UPR components may prevent loss of proteostasis, suggesting an avenue to delaying β-cell aging and preventing aging-related diabetes. Abstract : This single-cell transcriptomic study of aged pancreatic islet cells from cynomolgus monkeys reveals loss of proteostasis as a hallmark of β-cell aging.